Blind identification and digital calibration method of broadband receiver front-end nonlinearity - PENG Jun1; MA Hong1; JIN Jiang; HU Xiao1; PENG Liang1; ZHANG Hui1; GUO Wu-Jun1 (Tongxin xuebao)
A novel real-time digital nonlinearity post-calibration method was developed based on the Volterra series.With the purpose of fitting the inverse transfer function of the nonlinear distortion characteristics of the receiver,parameters of the model were measured and self-adaptively updated without knowledge of the inputs using the blind identification cri-terion that was aimed at the minimizing of the total energy of the frequencies other than strong signals in the calibrated outputs.Experimental results on multi-tone excitation and 16-QAM modulation input show that with the proposed method,spurs-free-dynamic-range（SFDR） of the high efficiency nonlinear receiver front-end would achieve almost 26dB improvement,and the ability of the system in weak signals detection can be also significantly enhanced.